An Agaricus Blazei Murill-based mushroom extract may be beneficial for athletes because it protects against inflammation, infection and allergy - Hetland, G. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Strenuous exercise suppresses cellular immunity and increases susceptibility to infections (1). In elite swimmers also the frequency of allergy, asthma and airway hyper-responsiveness is increased (2). This is explained by lower type-1/type-2 cytokine ratio in athletes (1) because type-1 protect against cancer and infect cytokines like IFNions whereas type-2 like IL-4 promote allergy and asthma. Agaricus bM (AbM) is an edible medicinal Basidiomycetes mushroom of Brazilian origin used in traditional medicine and cultivated commercially for its positive health effects. AbM is a known immunomodulator and has antitumor effects in mouse models (3). Recently, we have examined the effect of the AbM-based extract, AndoSanTM, on bacterial sepsis (3) and allergy (4) in mouse models, and inflammation in humans (5, 6). METHODS: AndoSanTM (www.immunopharma.org), a Japanese GMP-certified mushroom extract contaning 82% AbM, or saline was given orally (0.2 ml) to mice either sensitized s.c. with allergen ovalbumin (OVA), or challenged i.p. with lethal pneumococci or fecal bacteria. End points were serum IgE to OVA and cytokines in cultures of spleen cells from the mice, and bacteremia and survival, respectively. Plasma cytokines were measured in healthy volunteers and inflammatory bowel disease (IBD) patients who drank 60 ml AndoSanTM daily for 12d. RESULTS: In OVA-sensitized mice given AndoSanTM, serum IgE to OVA was lower and type-1/type-2 cytokine ratio higher in spleen cell cultures. AndoSanTM reduced bacteremia and increased survival compared with saline control; 50 vs 13% and 34 vs 0%, in the two models. In healthy volunteers and IBD patients AndoSanTM reduced pro-inflammatory cytokines like MIP-1, TNF and IL-1 in plasma. DISCUSSION: The positive effects obtained with AndoSanTM on infection, allergy and inflammation indicates that this AbM-based mushroom extract may improve health and training-related inflammation in elite swimmers and other athletes.